Implementing a HIPAA-Compliant Data Lake: Architecture and Best Practices - Sahini Dyapa (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The healthcare industry is experiencing a transformative shift in data management due to the implementation of cloud-based data lake solutions. This article explores the challenges, architecture, and best practices for implementing data lakes in healthcare settings, focusing on regulatory compliance, security frameworks, and operational benefits. The article examines how healthcare organizations adopt sophisticated data management systems to handle the increasing volume of electronic health records while maintaining strict security protocols. The article discusses integrating various data types within a unified architecture, including clinical information, administrative records, and real-time patient monitoring data. Furthermore, it analyzes the implementation of comprehensive security measures and compliance reporting frameworks essential for protecting sensitive patient information while enabling efficient healthcare delivery and research capabilities.